DELPHIC ORACLE, RAND CORPORATION AND DELPHI METHOD : DELPHIC ORACLE, RAND CORPORATION AND DELPHI METHOD - Ilieva , Sonya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The point of this article is to show what binds the Delphic oracle, the RAND Corporation and Delphi method. And the connecting link is the long-term forecasting. Since ancient times, people have sought to break into the future to build a rational life in the present. It is mentioned that this was done through the intuitive forecasting. Present offers another starting point for looking into the future that combines scientific intuition plus reliable statistics and mathematics and other models such as the method for long-term forecasting - Delphi method, developed by think tank RAND Corporation - USA. Thanks to its research capacity, the corporation established for decades that a highly effective forecasting method, reflecting the overall theoretical and experimental work in a series of reports. They become a kind of milestones for researchers from around the world to successfully apply it in their scientific and practical activities.